Information Design at the Library of Bina Nusantara University Anggrek Campus - Mahdi, Reza; Jakti, RA Diah Resita Kuntjoro (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
Library is a place to store book or non-books collections that can be used to research, read, and learn. At Bina Nusantara University, Anggrek campus, the library is also a space for discussion and sharing knowledge to each other. The spaces are large and includes large collection of books, causing considerable obstacles in the library of Bina Nusantara University Kampus Anggrek. This is because the important information for visitors has not been processed maximally. An open space at the library can be put with design information about the system of borrowing and returning books, also the other main services. We always see many signs in the street such as road sign, the rules in somewhere, or infographics of some directions. They are some example of information design. The library ofcourse can use that too to help the visitor in the library. For this research, we use the qualitative approach and the descriptive method by doing some observation in the library and some interview to students who visit the library, and also the Visual Communication Design lecture. So this research will discuss what are the information designs in the Library of Bina Nusantara University, Anggrek Campus and why the design of information is important.